Hubungan Tingkat Pengetahuan tentang Diabetes Melitus, Tingkat Asupan Karbohidrat dan Tingkat Asupan Serat dengan Kadar Glukosa Darah Postprandial pada Penderita Diabetes Melitus Tipe 2 Rawat Jalan RSUP Dr. Kariadi Semarang - Rahmawati, Pradina; Mintarsih, Sri Noor; Priyatno, Djoko (JURNAL RISET GIZI, 2013)
Background: the prevalence of type 2 diabetes mellitus in the province of Central Java in 2009 at 0, 19% experienced improvement when compared to the prevalence in 2008 of 0, 16%. incidence of diabetes mellitus is influenced by several factors. knowledge about the disease diabetes mellitus diabetes mellitus and its treatment is important in holding peranana control blood sugar levels. intake of carbohydrates and fiber that fits your needs can help control blood sugar levels. Purpose: This study aims to determine the relationship level of knowledge about diabetes mellitus, the level of carbohydrate intake and level of fiber intake with postprandial blood glucose levels in patients with type 2 diabetes mellitus poly outpatient department of Dr. Kariadi Semarang. Methods: the study design was cross sectional approach. Data rates of diabetes mellitus knowledge obtained by a questionnaire, the data rate of carbohydrate intake and level of fiber intake obtained by food frequency questionnaire semi-quantitative. data analysis using chi square test. Results: the results showed that all samples were aged over 40 years, the number of samples of postprandial blood glucose levels are high as 51.5%, the level of knowledge of diabetes mellitus with less category at 72.7% and a high level of carbohydrate intake 72.7 % and the level of fiber intake by as much as 72.7% less category. Conclusion: there is a relationship between the level of knowledge about diabetes mellitus in post prandial glucose levels, while the level of carbohydrate intake and level of fiber intake did not show any relationship with post-prandial blood glucose levels. need to make a referral to outpatients and provide counseling on a regular basis.